Wettability of shaleâbrineâH2 system and H2-brine interfacial tension for assessment of the sealing capacities of shale formations during underground hydrogen storage - Al-Mukainah, H. (Elsevier Ltd, 2022)
Replacement of fossil fuels with clean hydrogen has been recognized as the most feasible approach of implementing CO2-free hydrogen economy globally. However, large-scale storage of hydrogen is a critical component of hydrogen economy value chain because hydrogen is the lightest molecule and has moderately low volumetric energy content. To achieve successful storage of buoyant hydrogen at the subsurface and convenient withdrawal during the period of critical energy demand, the integrity of the underground storage rock and overlying seal (caprock) must be assured. Presently, there is paucity of information on hydrogen wettability of shale and the interfacial properties of H2/brine system. In this research, contact angles of shale/H2/brine system and hydrogen/brine interfacial tension (IFT) were measured using KrÃ¼ss drop shape analyzer (DSA 100) at 50 Â°C and varying pressure (14.7â1000 psi). A modified form of sessile drop approach was used for the contact angles measurement, whereas the H2-brine IFT was measured through the pendant drop method. H2-brine IFT values decreased slightly with increasing pressure, ranging between 63.68Â° at 14.7 psia and 51.29Â° at 1000 psia. The Eagle-ford shale with moderate total organic carbon (TOC) of 3.83 attained fully hydrogen-wet (contact angle of 99.9Â°) and intermediate-wet condition (contact angle of 89.7Â°) at 14.7 psi and 200 psi respectively. Likewise, the Wolf-camp shale with low TOC (0.30) attained weakly water-wet conditions, with contact angles of 58.8Â° and 62.9Â°, at 14.7 psi and 200 psi respectively. The maximum height of hydrogen that can be securely trapped by the Wolf-camp shale was approximately 325 meters whereas the value was merely 100 meters for the Eagle-ford shale. Results of this study will aid in assessment of hydrogen storage capacity of organic-rich shale (adsorption trapping), as well as evaluation of the sealing potentials of low TOC shale (caprock) during underground hydrogen storage. Â© 2022